Adsorbents in Nuclear Forensics (Review) - Vasylyeva, Hanna; Mironyuk, Ivan; Mykytyn, Igor (Physics and Chemistry of Solid State, 2024)
This paper reviews radiochemical methods for manufacturing radioactive sources produced by the Soviet Union between 1960 and 1990. It is concluded that the ideas of the most interesting developments were borrowed from foreign scientific journals. It is shown that synthetic zeolites have been proposed as carriers for 90Sr. Methods for creating 90Sr-90Y sources on synthetic zeolite carriers have been described. A review of other 90Sr-90Y sources was also made. Information about the production method of radioactive sources can be useful in nuclear forensics. One of the key characteristics of a radioactive substance is the “age” - the date of its production. In this paper, the term "age-dating" of radioactive materials or sources is defined, and formulas for calculating the time elapsed since the production of this source are given. For effective dating calculations, it is necessary to separate the parent and daughter radionuclides contained in the source. Therefore, the paper also provides a brief overview of modern adsorbents that can be used for the effective separation of radionuclides. Such adsorbents are commercial Dowex 1x8, TEVA, Sr Resin, DGA Resin, and titanium dioxide prototypes with unique properties. The general conclusion of the work is as follows: adsorbents in nuclear forensics can be both an object of research and a necessary material for the age-dating of unknown radioactive sources.